Nivel de actividad física y consumo de alcohol y tabaco en universitarios - Sagñay Tixi, Jhonnatan Armando (2025)
The present research work, titled "Level of Physical Activity and Alcohol and Tobacco Consumption in University Students," aimed to identify the relationship between pre-intervention and post-intervention v02max by applying a Physical Activity Program and the consumption of Alcohol and Tobacco in young university students. The results of the analysis and statistical interpretation of the fieldwork, as well as conclusions and recommendations regarding alcohol and tobacco and their impact on the physical activity level of young people, can be observed. This study was carried out at the National University of Chimborazo with students from the Medicine program. Validated tests were used, applied correctly, and given to the students. The research design was quasi-experimental, a method to establish causal connections between variables. The field research methodology involves collecting information in the natural environment where the phenomena being analyzed occur. Through analysis and a normality test, it was observed that the results showed a p-value of 0.00, which is highly significant. In this research, a 12-week program specifically designed for university students in the Medicine program at the National University of Chimborazo (fourth, fifth, and sixth semesters) was applied. Therefore, The hypothesis is mentioned, which suggests that there are changes in the intensity of physical activity after the intervention (there is a difference between the pretest and the post-test)